Study on using the hybrid cell a6g11c9 to produce the anti-a monoclonal antibody that agglunating a antigen on the surface of red blood cells - Trung, Nguyen Thi; Hai, Truong Nam (Academia Journal of Biology, 2017)
Almost of the ABO blood grouping reagents is being trading derive from the monoclonal antibodies. There are two methods to produce the monoclonal antibodies from hybridoma lines, which were in vitro method (hybridoma cultured in the medium) and in vivo method (hybridoma cultured in the mice intra-abdominal). In Vietnam, Nguyen Thi Trung and co-authors was succesfully screened in hybridoma cell line A6G11C9 which generating of the anti A monoclonal antibody agglutinated A antigen on the surface of red blood cells. The fusion of mouse lymohocyte B generated anti-A antibody with mouse myeloma sp2/0 is formed that hybrid cell lines. The anti-A monoclonal antibody is produced from hybridoma cell line A6G11C9 have been highly intensive confirmed. It is capability of growth and anti B monoclonal antibody producing stability through the generations. In this study, the process to produce large amounts of monoclonal antibodies from B4D10C9 hybridoma by in vitro method are published. Firstly, hybridoma cells are stored in liquid nitrogen to wake by culture in medium. Then, First, hybrid cells are stored frozen in liquid nitrogen to wake cultured cells. Then, they were first inoculated to produce enough biomass to serve a larger scale. Cell biomass continues to be second inoculated into DMEM containing 10% fetal bovin serum for 10 days. The culture medium contained anti-A monoclonal antibodies were collected by centrifugation to remove cells. The anti-A monoclonal antibody levels in culture medium was concentrated and remove phenol red indicator by the precipitation with NH4SO4 50% saturated. The anti-A monoclonal antibody solution at 5 times concentrated have been better agglutinated with erythrocytes containing A antigen than monoclonal antibody solution non-concentration. 150 ml of concentrated antibodies were produced. Antibody titer of the anti-A monoclonal antibodies in the concentrated 5 times solution was 1/512. The intensity of the reaction anti-A monclonal antibody with red blood cell containing A antigen was 4+. Citation: Nguyen Thi Trung, Truong Nam Hai, 2018. Study on using the hybrid cell a6g11c9 to produce the anti-a monoclonal antibody that agglunating a antigen on the surface of red blood cells. Tap chi Sinh hoc, 40(1): x-xx. DOI: 10.15625/0866-7160/v40n1.9154. *Corresponding author: tnhai@ibt.ac.vn Received 12 January 2017, accepted 20 December 2017